الحقوق الزوجية غير المالية في القانون الليبي: دراسة فقهية تحليلية - بوصيري، منى الصالحين عبدالسلام (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The study aims to shed light on non-financial marital rights in Libyan law. In this study, the researcher adopts two methods. Firstly, the inductive approach is used to extrapolate and track matters related to non-financial marital rights and the texts of the Libyan law. Secondly, it also adopts the analytical method to discuss and analyze the texts of Libyan law articles. This study finds that Libyan law concurs with the Hanafi doctrine on the permissibility of the testimony of women in the marriage contract. In 2015, Libyan legislators amended a number of articles, including Article 14, in which the impermissibility of women's testimony in the marriage contract is stated. Additionally, two male witnesses must be present in the contract. With this new amended act, Libyan law concurs with the majority of jurists' (fuqahaʼ) opinion because the marriage contract is not like any other contract. Libyan law also agrees with the majority of jurists (fuqahaʼ) on the issue of obligating cohabitation for both spouses, unlike the Hanbali doctrine, that sees it as desirable. Libyan legislators also removed Article 13 of the act, which stipulates the permissibility of polygamy. This is based on observations made by a team of senior scholars of Libya regarding the violation of some of the provisions of the Libyan personal status law of Islamic law. One of the jurists of Libyan law explains that Libyan legislators took the rule of this article from secular law, precisely from French law that prohibits marrying a second wife before the dissolution of the first marriage. Thus, the researcher suggests Libyan legislators to put this article within the amended articles, in the form that it will be compatible with Islamic law and reconsider its cancellation. The research concludes the study with a set of recommendations.